On the Back of Culture and Religion: The Oppression of Arab Women in Nawal El Saadawi’s Women at Point Zero - Olugbemi-Gabriel, Olumide; Dawodu, Sunday (Àgídìgbo: ABUAD Journal of the Humanities, 2017)
Nawal El Saadawi’s Women At Point Zero points eerily at the reality that in the Arab world which Egypt represents in the text, a trifecta of sex, religion and death forms the core of women oppression as espoused through the tragically unfortunate life of Firdaus, the novel’s major protagonist. This paper is therefore unequivocal in stating that the Arab world -through the canvas of Egypt- in the Saadawian text is a space for the pervasive oppression of women. The condition and oppression of women in the Arab world can be located within a toxic mix of culture and religion which has engendered virulent misogynistic attitudes towards women in general. In thislight, the paper embraces Feminism especially its radical strand as the most potent option available to any woman living in a fundamentally hostile space as the Arab world, where misogynistic attitudes are constructed deliberately by men’s contempt for women on the back of culture and religion.